Analisis Representasi Nilai Nilai Pancasila dalam Karya Seni Rupa: Lukisan Laskar Rakyat Mengatur Siasat Karya Affandi - Nova Ritonga; Mey Waty Aulia; Intan Mumtazah Assaa’idah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the representation of Pancasila values ​​in the painting Laskar Rakyat setting Siasat by Affandi. This painting is considered to have a strong philosophical meaning related to the struggle of the Indonesian people in maintaining independence. This study uses a qualitative method with a literature study approach (library research), where data is obtained from various written sources such as books, scientific journals, articles, and related documents. The data collection technique is carried out through the documentation method, while the data obtained is analyzed using content analysis techniques to identify symbols, colors, and visual elements that reflect the values ​​of Pancasila. The results of the study show that the painting Laskar Rakyat setting Siasat represents the five values ​​of Pancasila. The value of Belief in the One Almighty God is seen in the slogan